Mesoporous silica nanoparticles: synthesis methods and their therapeutic use-recent advances - Ghaferi, Mohsen; Koohi Moftakhari Esfahani, Maedeh; Raza, Aun; Al Harthi, Sitah; Ebrahimi Shahmabadi, Hasan; Alavi, Seyed Ebrahim (Journal of drug targeting, 2021)
Mesoporous silica nanoparticles (MSNPs) are a particular example of innovative nanomaterials for the development of drug delivery systems. MSNPs have recently received more attention for biological and pharmaceutical applications due to their capability to deliver therapeutic agents. Due to their unique structure, they can function as an effective carrier for the delivery of therapeutic agents to mitigate diseases progress, reduce inflammatory responses and consequently improve cancer treatment. The potency of MSNPs for the diagnosis and management of various diseases has been studied. This literature review will take an in-depth look into the properties of various types of MSNPs (e.g. shape, particle and pore size, surface area, pore volume and surface functionalisation), and discuss their characteristics, in terms of cellular uptake, drug delivery and release. MSNPs will then be discussed in terms of their therapeutic applications (passive and active tumour targeting, theranostics, biosensing and immunostimulative), biocompatibility and safety issues. Also, emerging trends and expected future advancements of this carrier will be provided.